Development of watermelon picking robot based on AioT - Yang Chenshuo; Zhang Pingchuan; Yu Hao; Xue Yang; Wang Wenjie; Xiao Shuquan (ITM Web of Conferences, 2025)
This project integrates 5G, IoT, and AI technologies to develop a watermelon picking robot, aiming to solve the issue of watermelon harvesting in agricultural fields. The robot features a hexapod walking mechanism. By combining machine vision with a fan, it can avoid crushing melon vines. It uses a watermelon maturity - processing algorithm to identify, pick, weigh, and code ripe watermelons. With 5G communication, the robot uploads field operation data to the cloud platform. The Beidou navigation system and A* algorithm enable its autonomous movement in the melon field. This innovation offers an advanced solution for China's watermelon - planting industry and actively contributes to rural revitalization.